Deconstructing Bentham’s Panopticon: The New Metaphors of Surveillance in the Web 2.0 Environment - Manuela Farinosi (tripleC: Communication, Capitalism & Critique)
This article reflects on the meaning of the words “control” and “privacy” in light of the intensive diffusion of user generated content on the web. It presents some results of an empirical research based on 145 essays written by Italian students. The data were analysed from a qualitative point of view to understand how young people frame the topic of control on web 2.0. The attention is focused on the metaphors used to describe online platforms and on the social environments they mention when they speak about the impacts of online diffusion of personal content on offline life. The results show that the new control practices cannot be adequately described within the classical framework of vertical control. The traditional panoptic principle of observation has to a certain extent been transformed and the Panopticon itself is no more an effective metaphor to describe the control dynamics on web 2.0.